Dual-gated BN-sandwiched multilayer graphene field-effect transistor fabricated by stamping transfer method and self-aligned contact - Park, Jeongmin; Kang, Haeyong; Chung, Dongsub; Kim, Joonggyu; Kim, Jeong-Gyun; Yun, Yoojoo; Lee, Young Hee; Suh, Dongseok (Current applied physics, 2015)
To fabricate a BN-sandwiched multilayer graphene field-effect transistor, we developed a self-aligned contact scheme in combination with optimized stamping processes for the stacking of two-dimensional (2D) materials. By using a self-aligned contact method during device fabrication, we can skip the dry-etch process which requires an exact etch-stop at the surface of the graphene layer and is not easy to control. In the structure of a dual-gate transistor, successful device operation at low temperature with and without magnetic fields proves that the self-alignment contact can be an effective tool for reliable device fabrication using 2D materials. •First demonstration of self-aligned contact scheme in the dual-gate (i.e. top and bottom gate electrodes) structure.•Stamping transfer technique without the dry-etch process for electrical contacts even in the hBN sandwiched structure.•Successful operation of dual gate showing the two local resistance maxima.•Observation of preliminary signal for conductance quantization in the low-temperature and the high magnetic field.